2017
DOI: 10.1002/jum.14371
|View full text |Cite|
|
Sign up to set email alerts
|

Establishing an Ultrasound Curriculum in Undergraduate Medical Education: How Much Time Does It Take?

Abstract: We describe the number of hours and instructors required to implement an ultrasound curriculum for undergraduate medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…An important question to be asked is how much time and effort are necessary to develop and implement such curricula. The University of Colorado School of Medicine aimed to address this issue by analyzing the time spent on teaching as well as types of instructors who contributed to their US curriculum 18 . They found that within an academic year, a combined total of 484 hours were spent teaching US to first‐ and second‐year medical students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important question to be asked is how much time and effort are necessary to develop and implement such curricula. The University of Colorado School of Medicine aimed to address this issue by analyzing the time spent on teaching as well as types of instructors who contributed to their US curriculum 18 . They found that within an academic year, a combined total of 484 hours were spent teaching US to first‐ and second‐year medical students.…”
Section: Discussionmentioning
confidence: 99%
“…They found that within an academic year, a combined total of 484 hours were spent teaching US to first‐ and second‐year medical students. Most of the faculty who volunteered were from the fields of emergency medicine, family medicine, and radiology, and 1 instructor was needed for every 8 students 18 . In our institution, radiologists and radiology residents are actively involved in developing and teaching radiology and anatomy courses to medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Then they progress to practical skills sessions at the bedside or simulation environments to image specific anatomy [1][2][3][4]. While some authors note discussion of image production/ orientation, sonographic planes, and imaging/scanning techniques [5][6][7][8][9][10][11], these discussions do not allow for reproducible detail, nor do such concepts seem to be the isolated focus of a practical skills session. The psychomotor skills involved with obtaining a 2-dimensional ultrasound image and successfully creating a 3-dimensional conceptualization of the structure being scanned requires having both baseline knowledge of the images that are being sought, as well as an understanding of how transducer movement impacts the images produced [12].…”
Section: Introductionmentioning
confidence: 99%
“…This as well as the CanMeds [5] demand qualified doctors to be capable of performing B-mode ultrasound examination in the case of emergency or less complex diseases. As a consequence, many universities now try to provide the bulk of bedside sonography training earlier, sometimes starting in the first year of undergraduate education [6][7][8][9]. Nevertheless, students' education regarding diagnostic abdominal ultrasound is insufficient [10].…”
Section: Introductionmentioning
confidence: 99%